Theory and Solutions of Heat Pulse Method for Determining Soil Thermal Properties. Issue 5 (February 2020) - Wang, Jiaming; He, Dong; Dyck, Miles; He, Hailong
Abstract: Information on thermal properties of soil is of paramount importance for environmental and earth science, and engineering. The heat pulse (HP) method has become the key technology for accurate determination of soil thermal properties and a variety of other physical properties (e.g., water content, bulk density, and water flux) in both laboratory and field environments. The HP method is a transient method that is commonly based on the analytical solutions to the radial heat flow equation when a line-heat source is applied. Over the past few decades, great endeavors have been devoted to advance the HP method. For example, the evolution and development in probe design, data logging equipment, data interpretation and computing capability has remarkably improved the accuracy and ease of use for determining soil thermal properties. However, there is a lack of study collating and synthesizing the development of the theory/solutions to obtain thermal properties of soil using the HP method. In this paper, we review the fundamental theories and solutions of the HP method, including differences and similarities of theories and applications between instantaneous line heat source (ILHS) and short-duration line heat-source (SLHS), between dual-probe heat-pulse (DPHP) and single-probe heat-pulse (SPHP) methods, and between the non-linear model fit (NMF) method and single point (SPM) method for data interpretation. In addition, the numerical solutions and semi-analytical solutions are also presented to provide heat pulse users information for selecting the best-fit method to meet their goals.